(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Contact lenses (CLs) are widely used ophthalmic devices that offer numerous benefits, such as improved cosmesis, expanded visual field, and enhanced vision without the drawbacks associated with spectacles. However, improper use of CLs can lead to complications, including corneal abrasions, ulcers, conjunctivitis, and keratitis, with severe cases resulting in blindness due to microbial keratitis and endophthalmitis. Despite the advantages, misuse of CLs due to a lack of knowledge and non-prescription acquisition poses significant risks to users. Objectives: This study aims to assess the level of knowledge regarding CL complications among the Saudi Arabian population and to identify the gaps in knowledge that may contribute to the misuse of CLs. Methods: A crosssectional study was conducted from July 2024 to March 2025 across various regions in Saudi Arabia. A total of 386 adult Saudi citizens, selected through a simple random sampling method, participated. Data were collected using a validated, self-administered online survey comprising sociodemographic information and knowledge assessment questions about CL use, its complications, and factors that increase the risk of developing complications. The survey instrument was pilot-tested with 20 individuals to ensure clarity and feasibility. Data analysis was performed using statistical software to evaluate the level of knowledge and identify significant associations between sociodemographic variables and knowledge levels. Results: This study assessed knowledge and awareness of CL complications among the Saudi Arabian population. Among 386 participants, 62.7% had high knowledge, 16.6% moderate, and 20.7% low knowledge, despite 48.7% showing high awareness. Women and employment had significantly higher knowledge levels (P < 0.05), while other sociodemographic factors were not statistically significant. Key misconceptions included misunderstanding CL hygiene and risk factors. The findings highlight critical knowledge gaps despite awareness, emphasizing the need for targeted educational interventions to improve CL safety and reduce preventable complications through public health campaigns and optometric counseling in Saudi Arabia. Conclusion: The findings of this study highlight significant gaps in knowledge and awareness regarding CL complications among the Saudi population. Despite a relatively high level of awareness, the lack of understanding concerning specific risk factors and proper care practices poses a risk for increased complications.